Persuasive Appeals: Influence of Digital Advertisements on Consumer Attitude Diversion in E-Shopping - Dr. Qamar Abbas; Komal Mehreen; Abdul Basit (Journal of Applied Research and Multidisciplinary Studies, 2025)
Digital advertising is one sector of marketing that is swiftly advancing. Marketers and academics are now paying monumental attention this mode of advertising because it is one of the most effective instruments of lure and persuasion of consumer in the digital era. Regulators have now turned to devising varied ways of exploiting digital platform to maximize profitability and that digital advertisements become the blood line to any business to maneuver consumer online buying behavior. The current study will seek to establish persuasive appeal of online advertisements that affect the degree of attitude diversion in consumers towards e-shopping. An example of a cross-sectional study design has been employed to gather quantitative data on a sample of 1270 students selected out of the top six public universities in KP, Pakistan, using a multistage stratified sampling technique. The information was collected by the help of self-designed questionnaires and analyzed with Simple Linear Regression. The statistical analysis shows that the extent of the attitude diversion of the consumers in the cognitive, affective, and conative dimension is greatly influenced by the nature of digital advertisements, which will eventually influence their intentions to purchase online.